Cholecystectomy and digestive cancer in Chile: complementary results from interrupted time series and aggregated data analyses - González, Constanza; García-Pérez, Alfonso; Nervi, Bruno; Munoz, César; Morales, Erik; Losada, Hector; Merino-Pereira, Gina; Rothhammer Engel, Francisco; Lorenzo Bermejo, Justo (International journal of cancer, 2025)
Gallbladder cancer (GBC) mortality in Chile is among the highest worldwide. In 2006, the Chilean government launched a programme guaranteeing access to gallbladder surgery (cholecystectomy) for patients aged 35-49 years. We evaluated the impact of this programme on digestive cancer mortality. After conducting an interrupted time series analysis of hospitalisation and mortality data from 2002 to 2018 publicly available from the Chilean Department of Health Statistics and Information, we calculated the change in the proportion of individuals without gallbladder since 10 years. We then estimated age, gender, region, and calendar-year standardised mortality ratios (SMRs) as a function of the change in the proportion of individuals without gallbladder. The cholecystectomy rate increased by 45 operations per 100,000 persons per year (95%CI 19-72) after the introduction of the health programme. Each 1% increase in the proportion of individuals without gallbladder since 10 years was associated with a 0.73% decrease in GBC mortality (95% CI −1.05% to −0.38%), but the negative correlation was limited to women, southern Chile and age over 60. We also found decreasing mortality rates for extrahepatic bile duct, liver, oesophageal and stomach cancer with increasing proportions of individuals without gallbladder. To conclude, 12 years after its inception, the Chilean cholecystectomy programme has markedly and heterogeneously changed cholecystectomy rates. Results based on aggregate data indicate a negative correlation between the proportion of individuals without gallbladder and mortality due to gallbladder and other digestive cancers, which requires validation using individual-level longitudinal data to reduce the potential impact of ecological bias.